2013
DOI: 10.1093/jxb/ert424
|View full text |Cite
|
Sign up to set email alerts
|

The paralogous SPX3 and SPX5 genes redundantly modulate Pi homeostasis in rice

Abstract: The importance of SPX-domain-containing proteins to phosphate (Pi) homeostasis and signalling transduction has been established in plants. In this study, phylogenetic analysis revealed that OsSPX3 and OsSPX5 (SPX3/5) are paralogous SPX genes (SYG1/Pho81/XPR1) in cereal crops. SPX3/5 are specifically responsive to Pi starvation at both the transcriptional and post-transcriptional levels. Similar tissue expression patterns of the two genes and proteins were identified by in situ hybridization and the transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 38 publications
2
79
0
Order By: Relevance
“…While at a low cellular Pi concentration, SPX4 is degraded through the proteasome pathway, resulting in increased targeting of PHR2 to the nucleus and enhancing its PIBSbinding ability, which eventually leads to the up-regulation of PSI genes. Additionally, SPX3 and SPX5 were indicated to be repressors of PHR2, although the precise mechanism remains to be determined (33). We note that the induced transcript levels of PSI genes and the enrichment of PHR2 binding on the IPS1 promoter in spx1spx2 under +P conditions have not reached their induced levels under −P conditions in WT (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…While at a low cellular Pi concentration, SPX4 is degraded through the proteasome pathway, resulting in increased targeting of PHR2 to the nucleus and enhancing its PIBSbinding ability, which eventually leads to the up-regulation of PSI genes. Additionally, SPX3 and SPX5 were indicated to be repressors of PHR2, although the precise mechanism remains to be determined (33). We note that the induced transcript levels of PSI genes and the enrichment of PHR2 binding on the IPS1 promoter in spx1spx2 under +P conditions have not reached their induced levels under −P conditions in WT (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Additional evidence in support of this premise comes from a yeast 2-hybrid screen that identified ubiquitin conjugase protein 8 as an NLA-interacting protein, and bimolecular fluorescence complementation analysis revealed that these two proteins interacted specifically in nuclear speckles (Peng et al 2007a). Previous studies have shown also that there is an extensive transcriptome response in Arabidopsis that is triggered by nitrogen limitation and regulated by NLA (Peng et al 2007b), and given that other members of the plant SPX-domaincontaining protein family are known to function, at least in part, in the nucleus by interacting (via their SPX domains) with transcription factors that control the phosphate starvation pathway (Wang et al 2004b;Lv et al 2014;Shi et al 2014) Given the complex subcellular targeting of NLA, the aim of the current study was to conduct a detailed mutational assessment of the distinct functional/structural domains in NLA to determine their role(s) in the protein's function and/or subcellular localization. Each of the mutant proteins was assessed to determine its subcellular localization, as well as its ability to functionally complement the low-nitrogen phenotype of nla mutant plants.…”
Section: Mutants Harboring Disruptions In the Phosphate Transporter Tmentioning
confidence: 99%
“…Wang et al, 2009;Liu et al, 2010). Recently, SPX3 and SPX5 were also demonstrated to be functional repressors of PHR2, although the precise mechanism remains to be determined (Shi et al, 2014).…”
Section: Spx4 Is a Key Component In The Regulation Of Phosphate Signamentioning
confidence: 99%
“…Wang et al, 2009). Although it has been genetically demonstrated that SPX1, SPX3, and SPX5 in rice are involved in the negative regulation of PHR2 (Liu et al, 2010;Shi et al, 2014), the mechanisms of the negative regulation and the different functions of these SPX proteins have not been discovered.…”
Section: Introductionmentioning
confidence: 99%